2016
DOI: 10.1074/jbc.m116.739953
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Remodels Overexpressed Functional Amyloids in Pseudomonas aeruginosa and Increases Biofilm Susceptibility to Antibiotic Treatment

Abstract: Epigallocatechin-3-gallate (EGCG) is the major polyphenol in green tea. It has antimicrobial properties and disrupts the ordered structure of amyloid fibrils involved in human disease. The antimicrobial effect of EGCG against the opportunistic pathogen Pseudomonas aeruginosa has been shown to involve disruption of quorum sensing (QS). Functional amyloid fibrils in P. aeruginosa (Fap) are able to bind and retain quorum-sensing molecules, suggesting that EGCG interferes with QS through structural remodeling of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 81 publications
5
76
1
2
Order By: Relevance
“…This is consistent with previous reports in which treatment with EGCG was performed in already formed aggregates 16,17,56 . This effect was not only reported for aSyn, but also for other amyloidogenic proteins, such as AB and γ-synuclein (gSyn) 16, 56,57 . Such effects are in agreement with the proposed mechanism of action for EGCG, whereby it mediates the reorientation of bonds between ordered protein molecules, leading to amyloid remodeling and the appearance of unordered, amorphous protein aggregates 17,58 .…”
Section: Discussionmentioning
confidence: 70%
“…This is consistent with previous reports in which treatment with EGCG was performed in already formed aggregates 16,17,56 . This effect was not only reported for aSyn, but also for other amyloidogenic proteins, such as AB and γ-synuclein (gSyn) 16, 56,57 . Such effects are in agreement with the proposed mechanism of action for EGCG, whereby it mediates the reorientation of bonds between ordered protein molecules, leading to amyloid remodeling and the appearance of unordered, amorphous protein aggregates 17,58 .…”
Section: Discussionmentioning
confidence: 70%
“…EGCG also inhibits PAO1 FapC amyloid formation by stabilizing pre-fibrillar oligomers, and it structurally remodels existing fibrils in vitro through the formation of non-amyloid aggregates [13]. To investigate the effect of EGCG on fibril formation of FapC WT and R3, desalted protein stocks were diluted in Tris buffer with various concentrations of EGCG.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm-associated bacteria, in particular, utilize amyloids as a building material to reinforce the EM and resist dispersion by chemical or mechanical agents [8, 11]. These fibrils may also promote antibiotic resistance and act as a reservoir for small molecules involved in quorum sensing [12, 13]. Amyloid fibrils polymerize in the absence of an energy source, so they serve as a metabolically advantageous molecular scaffold despite the limited resources of the EM environment [14].…”
Section: Introductionmentioning
confidence: 99%
“…When P1 and/or WapA are completely absent due to gene deletion, amyloid inhibitors have a diminished impact on biofilm formation compared to untreated cells because their targets of activity are gone, and the glucans can mediate cell-cell and cell-substratum interactions unhindered by monomeric or oliogomeric P1 and WapA. It has been reported that EGCG disrupts the ability of P. aeruginosa Fap to form amyloid fibrils by stabilizing protein oligomers [59]. In addition, these authors found that treatment of P. aeruginosa biofilms with EGCG decreased the minimal bactericidal concentration of tobramycin, an effect that was amplified when fap genes were overexpressed.…”
Section: Discussionmentioning
confidence: 99%